An investigation on plasma progesterone levels during pregnancy and at parturition in the Ivesi sheep - Kalkan, C.; Çetin, H.; Kaygusuzoglu, E.; Yilmaz, B.; Çiftçi, M.; Yildiz, H.; Öcal, H. (My University, 1996)
In this study, plasma progesterone concentrations in a total of 45 Ivesi sheep were investigated during pregnancy and at parturition. Blood samples were collected from all the sheep studied every 20 days commencing on the 30th day of pregnancy. Plasma progesterone levels were determined by radioimmunoassay. During the second half of the pregnancy, progesterone concentrations in the sheep giving birth to one, two and three lambs were 2.02 ± 0.08 ng/ml, 3.24 ± 1.18 ng/ml and 4.90 ± 0.85 ng/ml, respectively. There was no significant variation in progesterone levels between sheep with male and female offspring. At parturition, plasma progesterone concentrations did not differ significantly between the animals. The present results indicate that plasma progesterone levels could be used not only to determine the pregnancy status of the animal but also to predict the number of fetuses after the second half of the pregnancy.
Keywords: Fetuses; Parturition; Pregnancy; Progesterone; Sheep